From the environmental identity to the behavior: The status of pre-service science teachers - Esra Kızılay; Nagihan Tanık Önal (International Journal of Evaluation and Research in Education (IJERE), 2019)
In this research, the environmental identity of pre-service science teachers and their behaviors towards environmental problems were examined according to gender and grade. In the study, a path diagram is formed by evaluating the relationship between the variables. 215 pre-service science teachers of a university in Turkey, have participated in the study. The Environmental Identity Scale and the Environmental Problems Behaviour Scale were used as data collection tools. In the research, it was found that female students' averages environmental identity score was higher than males’ average score. There was no significant difference between pre-service teachers' environmental identity according to grade. It was found that female students’ average behavior score towards environmental problems was significantly higher than the average score of males. In the study, it was found that the average behavior scores towards environmental problems of the pre-service science teachers who are in the third and fourth grade were significantly higher than the average scores of the first and second-grade students. The research revealed a moderate relationship between pre-service science teachers' environmental identity and their behaviors towards environmental problems. 18% of the change in the behaviors of pre-service teachers towards environmental problems can be explained by their environmental identity